Endovascular Coil Embolization After Clipping: Endovascular Treatment of Incompletely Clipped or Recurred Cerebral Aneurysms - Chung, Jaehwan (Korean Society of Cerebrovascular Surgeons; Society of Korean Endovascular Neurosurgeons, 2014)
OBJECTIVE: The presence of a cerebral aneurysm remnant after surgical clipping is associated with a risk of regrowth or rupture. For these recurred aneurysms, coil embolization can be considered as a treatment option. We retrospectively reviewed cases of ruptured or regrown aneurysms after clipping treated by endovascular coil embolization. MATERIALS AND METHODS: We conducted a retrospective review of patients with ruptured or recurred aneurysm after clipping, who underwent coil embolization between January 1995 and December 2013. We evaluated clinical information and the outcomes of these cases. RESULTS: Eight patients were treated by endovascular coil embolization after surgical clipping. Six aneurysms were located in the anterior communicating artery, one in the posterior communicating artery, and one in the middle cerebral artery bifurcation. All patients were initially treated by surgical clipping because of a ruptured aneurysm. Aneurysm recurrence at the initial clipping site was detected in all cases. The median interval from initial to second presentation was 42 months. In four patients, aneurysms were detected before rupture and the four remaining patients presented with recurrent subarachnoid hemorrhage. All patients were treated by coil embolization and showed successful occlusion of aneurysms without complications. CONCLUSION: Endovascular coil embolization can be a safe and successful treatment option for recurred aneurysms after clipping.